2021
DOI: 10.1111/jpn.13485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary cellobiose on the intestinal microbiota and excretion of nitrogen metabolites in healthy adult dogs

Abstract: In order to evaluate the potential prebiotic effects of cellobiose, 10 healthy adult research beagle dogs received a complete diet containing 0, 0.5 and 1 g cellobiose/kg bodyweight (BW)/day. At the end of each feeding period, faeces, urine and blood of the dogs were collected. The results demonstrated a significant increase of faecal lactate concentrations, indicating a bacterial fermentation of cellobiose in the canine intestine. Along with this, a dose-dependent linear increase of the relative abundance of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…Considering the increase in Lactobacillus , this data is unexpected. Indeed, the increase in the lactate concentrations in the faeces of the dogs indicates a promotion of lactic acid bacteria in the intestine, demonstrating a linear increase in Lactobacillaceae [ 57 ]. Concerning the ammonia results, the HL1 group reported a significant decrease in the ammonia value compared with the HS and HL2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the increase in Lactobacillus , this data is unexpected. Indeed, the increase in the lactate concentrations in the faeces of the dogs indicates a promotion of lactic acid bacteria in the intestine, demonstrating a linear increase in Lactobacillaceae [ 57 ]. Concerning the ammonia results, the HL1 group reported a significant decrease in the ammonia value compared with the HS and HL2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…It might also be possible to assume that these results may have been caused by the presence of secondary compounds in hemp. Indeed, Cannabis sativa plants and co-products contain a multitude of chemicals, including phytocannabinoids, terpenoids, flavonoids, and sterols [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that Firmicutes , Bacteroidetes , Fusobacteria , Proteobacteria and Actinobacteria were the main genera in dogs, which was the same as that reported by Paßlack et al . [ 15 ]. There have been many studies on the influence of food processing methods on animal intestinal microbiota [ 4 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The instructions of the manufacturer were followed, with the exception of a lysis step at 90 • C. For amplicon sequencing, the V3-V4 region of the 16S rDNA gene was targeted, and the 16S rDNA sequences were finally analyzed with the QIIME2 pipeline [13] and the SILVA SSU database [14]. More details on the method used are provided by Paßlack et al [15]. The full data set of the sequencing is available at the NCBI BioProject database under ID PRJNA755187.…”
Section: Fecal Microbiota and Microbial Metabolitesmentioning
confidence: 99%
“…The indoxyl sulfate concentrations were measured in the plasma using the method of Chen et al [18] and highperformance liquid chromatography (HPLC Agilent 1100, Agilent Technologies, CA, USA). The phenol and indole concentrations in the plasma were also measured with the HPLC Agilent 1100 (Agilent Technologies, CA, USA), more details are provided by Paßlack et al [15]. The urinary phenol and indole concentrations were determined by gas chromatography (GC 6890 N, Agilent Technologies), as specified by Eisenhauer et al [19].…”
Section: Plasma and Urine Analysismentioning
confidence: 99%